Project proposal for Anglo Platinum to make a meaningful switch to G3 sustainable development reporting : a logical framework analysis - Bullock, Stephen (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Public Management and Planning))--University of Stellenbosch, 2009.